Role of soil carbon in the landscape functioning of the Alto São Bartolomeu watershed in the Cerrado region, Brazil - Alves, Ray Pinheiro; Junior, Antonio Felipe Couto; Martins, Eder de Souza; Nardoto, Gabriela Bielefeld (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of soil carbon on landscape functioning of the Oxisols covering the plateaus of the Alto São Bartolomeu watershed, in the Cerrado (Brazilian savanna) region of Central Brazil. Soil organic carbon (SOC) concentration, carbon stocks, and some soil physical and chemical characteristics were determined at the 0–0.20-m depth on native and anthropogenic areas. Soils from cerrado stricto sensu patches were similar both physically and chemically, being affected by exchangeable Al3+ and by SOC concentrations, while anthropogenic matrices were affected by soil bulk density, pH, extractable P, and exchangeable Ca2+ and Mg2+. The estimate of spatial distribution of soil carbon better fitted had an adjusted R2 of 64.49% using soil C stock and 66.50% using SOC concentration from native and anthropic areas. Estimating SOC concentration from soil and landscape types, using geotechnologies to analyze vegetation indices, is a potential tool to evaluate the productivity of different agroecosystems, besides contributing to make management strategies more suitable on large scales.